Approach to Treatment of Multiple Sarcoids in Crioulo Horses - Kuwer Jacobsen, Tainã; De Bastiani, Grasiela; de Vargas, Marjorie; Szpoganicz da Silva, Mateus; Lucio Fontana Goetten, André; Moraes Figueiró, Giuliano; Tony Ramos, Adriano (Acta Scientiae Veterinariae, 2020)
Background: The equine sarcoid corresponds to one third of equine tumors, and may present as single or multiple and in six different shapes. The etiology is still unknown, but it brings with it some predisposing factors. Confirmatory diagnosis is made based on histopathology evaluation. There are several treatments described in the literature, therefore, it varies according to the choice of the veterinarian, the conditions and interests of the owner and the characteristics of the sarcoid tumor. The present research work aims to report the case of a Crioule horse that presented of a multiple sarcoids in different shapes of the body and, testing the efficacy and response to the chosen treatment. Case: The Crioulo gateado coat stallion, aged six years and seven months and weigh 360 kg. In the physical evaluation observed alert behavior, body score (ECC) three (1-5), 36 bpm, 20 mpm. The pelvic right limb (PRL) presented a mobile fibroblastic nodule was found on the proximal dorsal face of the third metatarsal bone (MTIII), pendular and broad-based, ulcerated, with a diameter of approximately 10 cm x 7 cm associated of a dark pink color. Likewise, on the caudal surface of the ear observed verrucous sessile flat lesion with a diameter of 5 cm and, in the right corner of the mouth, a non-ulcerated, pendular, mobile dark red color nodule evidenced with a diameter approximately 3 cm. Similarly, there were multiple ulcerated pendulous dark pink color mobiles nodules in the region of the left and right groin, as well in the pectoral region. For histopathological evaluation, a 0.5 cm specimen tumor of the medial corner of the mouth was collected and observed proliferation of connective tissue and thickening of the epidermis with pseudocarcinomatous projections suggestive of sarcoid lesion tumor. Subsequently, surgical removal tumors associated with cryotherapy and application of 0.25 ml of intralesional vincristine to each region. In addition, an autologous implant tumors specimen of the 0.3 cm approximately was performed after 15 minutes cryopreservation. They were implanted of the subcutaneous neck space in 1 cm incisions and synthesis with simple interrupted pattern using 2-0 nylon. As postoperative PRL care consisted of the utilization Robert Jones bandage for 20 days period, with changes and wound care in an interval of 4 days associated with the daily antisepsis care of the other treated areas. The patient evaluated 10 months after the aforementioned procedures and complete healing tumors lesions. Discussion: The etiology of the sarcoid not well defined, but there are some predispositions such as race, handling of animals and the location of the body. The accompanied animal falls within the aforementioned predispositions observed in this case characterized of the association breed cattle. Probably the sarcoid tumors to be related together of the bovine papillomavirus, and was affected in the most cited regions, such as members, mouth and ears. The sarcoid can appear in six different shapes, several of which can be found in the same animal. Among the treatments mentioned, we opted for the association of surgical removal, associated with cryotherapy and the use of intralesional vincristine, in addition to autologous implants and topical use of Acyclovir. Considering that there have been no recurrences at this moment, the treatment was effective in eliminating the sarcoid tumors and making it a good option for the control lesions of the clinically presented high rates of recurrences.